2015
DOI: 10.1371/journal.pone.0132056
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Initiation of Treatment for Chronic Hepatitis C Infection in United States Veterans, 2004–2009

Abstract: We describe the rates and predictors of initiation of treatment for chronic hepatitis C (HCV) infection in a large cohort of HCV positive Veterans seen in U.S. Department of Veterans Affairs (VA) facilities between January 1, 2004 and December 31, 2009. In addition, we identify the relationship between homelessness among these Veterans and treatment initiation. Univariate and multivariable Cox Proportional Hazards regression models with time-varying covariates were used to identify predictors of initiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
1
7
1
Order By: Relevance
“…The low overall treatment rate of 11.9% is consistent with those published for the USA, Canada and Australia, with these published rates ranging from 1.1% to 25.6% . Those studies identified a number of factors associated with treatment initiation, with older age, current drug and alcohol use, and comorbidities being associated with a reduced likelihood of treatment. In addition, patients reported deferring treatment until the availability of better therapies, because of treatment‐related perceptions, ability to comply and concerns with side effects …”
Section: Discussionsupporting
confidence: 82%
“…The low overall treatment rate of 11.9% is consistent with those published for the USA, Canada and Australia, with these published rates ranging from 1.1% to 25.6% . Those studies identified a number of factors associated with treatment initiation, with older age, current drug and alcohol use, and comorbidities being associated with a reduced likelihood of treatment. In addition, patients reported deferring treatment until the availability of better therapies, because of treatment‐related perceptions, ability to comply and concerns with side effects …”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, genotype did not significantly affect treatment decision in the Korean population (58.3% in GT 1 vs 61.7% in GT 2, p=0.302, data now shown), which was not consistent with previous studies 13,20. In this multicenter study, the decision to initiate treatment was based on each physician’s preference, which may have put different emphasis on genotype when deciding to initiate antiviral treatment.…”
Section: Discussioncontrasting
confidence: 71%
“…A recent U.S. study including 101,444 Veterans showed that treatment initiation rate was very low (7.4%), and those with genotype 2/3, non-white race, and Medicare or other insurances were correlated with high treatment initiation rates. 13 In a recent Taiwan study, the treatment rate was 13.7% in the estimated HCV-viremic population of 554,361. 8 The treatment initiation rate reported in this study was much higher than in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1 , a total of 39 studies with 476,443 CHC patients (37 articles and 2 abstracts) met eligibility criteria and were included in our primary meta-analyses. [ 3 , 4 , 6 , 7 , 14 48 ] Most studies were from North America (19/39, 49%) or Europe (11/39, 28%). Eight (21%) were from the Asia or Pacific regions.…”
Section: Resultsmentioning
confidence: 99%
“…Several U.S. based studies report treatment rates with pegylated-interferon (PEG-IFN) and ribavirin (RBV) that range from nine to 36%. [ 3 7 ] In their report the WHO also estimates that under 1% of treatment eligible CHC patients worldwide have received antiviral therapy. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%